Profile of MSMEs in East Java: challenges and prospects - Kurniawan, Dhika Amalia; Cahyo, Eko Nur; Maulan, Suharni; Yaya, Rizal (UMY Press, 2020)
This chapter aims to explore further information about the background, the profile of the MSME’s sector in East Java. The identification results can be utilized in various ways: policy formulation, identify problems MSMEs, map-ping of a strategy to build competitive advantage for MSMEs. This chapter applied a quantitative approach and the data collection techniques used are survey methods using questionnaires. Data analysis techniques are a descrip-tive statistical test. The sample used is mostly MSMEs in East Java (according to) the number of samples used by 250 respondents. This chapter shows that the profile of MSME business actors (key players) in East Java can be viewed from the perspective of gender differences, MSMEs were dominated by re-spondents’ female spouses surveyed. Based on the aspect of Marital Status, MSME is dominated by married respondents with a percentage of 81.6%, Based on the aspect of age distribution, SMEs are dominated by respondents aged 40-49 years, with a percentage of 37.6%. Based on the aspect of Edu-cation Level, East Java MSME was dominated by respondents with high school level education with a percentage of 62.8%. Based on the aspect of owner-ship of expertise (what do you mean?) before entrepreneurship, MSME with the same percentage, the respondents already have expertise in entrepre-neurship and some do not have expertise before becoming entrepreneurs. Based on the aspect of the number of full time workers in their business, East Java MSME has only one worker in their business operations, with a percent-age of 40.8%. Based on the aspect of income, MSME has amassed between 11 million and 50 million per year with a percentage of 28.4%. Based on the aspect of the duration works carried out, MSMEs has been working for more than 10 years, with a percentage of 55%. Based on the aspect of Total assets in business, MSME has assets of 500 thousand - 50 million with a percentage of 67,2%. Based on the aspect of the establishment of the business, East Java MSME entrepreneurs set up businesses in 2011 to 2018 with a percentage of 61.2%. Based on the aspect of the form of the business entity , East Java MSME has individual / private business entities, with a percentage of 60%. Based on the aspect of the type of business sector, MSMEs entrepreneurs are worked in the trade and services sector, with a percentage of 38.4%.